The impact of government subsidy and tax policy on the competitive decision-making of remanufacturing supply chains. Issue 1 (2nd January 2019) - Li, Zhen; Zheng, Wei; Meng, Qingfeng; Jin, Shuai
Abstract: In this paper, we consider a two-period competition model of a remanufacturing supply chain consisting of three members: a new product manufacturer, a recycler and a remanufacturer. The manufacturer supplies new products in the first period and the remanufacturer participates in the competition in the second period. We consider three scenarios in the second period: (1) there is no government subsidy in the competition; (2) there is only government subsidy in the competition; (3) there are both government subsidy and tax in the competition. First, we give the optimal decision-making of the manufacturer, the remanufacturer and the government in the three scenarios; second, we analyse changes in the decision-making of the manufacturer and remanufacturer in the three scenarios and compare their results. We analyse the effects of government subsidy and tax and their asymmetric use on manufacturers' and remanufacturers' decision-making variables and competitive performance. We also take consumer awareness of environmental protection into account and examine its impact on subjects' decisions. Lastly, we operate a numerical example to show the results.